Localization-associated immune phenotypes of clonally expanded tumor-infiltrating T cells and distribution of their target antigens in rectal cancer. (3rd June 2019) - Penter, Livius; Dietze, Kerstin; Ritter, Julia; Lammoglia Cobo, Maria Fernanda; Garmshausen, Josefin; Aigner, Felix; Bullinger, Lars; Hackstein, Holger; Wienzek-Lischka, Sandra; Blankenstein, Thomas; Hummel, Michael; Dornmair, Klaus; et al.
ABSTRACT: The degree and type of T cell infiltration influence rectal cancer prognosis regardless of classical tumor staging. We asked whether clonal expansion and tumor infiltration are restricted to selected-phenotype T cells; which clones are accessible in peripheral blood; and what the spatial distribution of their target antigens is. From five rectal cancer patients, we isolated paired tumor-infiltrating T cells (TILs) and T cells from unaffected rectum mucosa (TUM ) using 13-parameter FACS single cell index sorting. TCRαβ sequences, cytokine, and transcription factor expression were determined with single cell sequencing. TILs and TUM occupied distinct phenotype compartments and clonal expansion predominantly occurred within CD8 + T cells. Expanded TIL clones identified by paired TCRαβ sequencing and exclusively detectable in the tumor showed characteristic PD-1 and TIM-3 expression. TCRβ repertoire sequencing identified 49 out of 149 expanded TIL clones circulating in peripheral blood and 41 (84%) of these were PD-1 − TIM-3 − . To determine whether clonal expansion of predominantly tumor-infiltrating T cell clones was driven by antigens uniquely presented in tumor tissue, selected TCRs were reconstructed and incubated with cells isolated from corresponding tumor or unaffected mucosa. The majority of clones exclusively detected in the tumor recognized antigen at both sites. In summary, rectal cancer is infiltrated with expanded distinct-phenotype T cell clones that either i) predominantly infiltrate the tumor, ii) predominantly infiltrate the unaffected mucosa, or iii) overlap between tumor, unaffected mucosa, and peripheral blood. However, the target antigens of predominantly tumor-infiltrating TIL clones do not appear to be restricted to tumor tissue.